Effect of Chemical Crosslinking on the Biodegradation Rate of Kraft Paper - Antti Korpela; Atsushi Tanaka; Jaakko Asikainen (BioResources, 2023)
Wood-based paper fibers are inherently biodegradable. In contact with moist soil and in compost, papermaking fibers are readily broken down by soil microbes. Resistance to biodegradation is needed, as paper is used for special applications such as mulching in agriculture and forestry, the coating of construction materials, and for packing and wrapping under conditions where packaging materials may be exposed to contact with moist soil or other type microbial active contamination. A preceding study showed that paper chemical crosslinking with glyoxal, citric acid (CA), or methylated 1,3-dimethylol-4,5-dihydroxyethylene urea (mDMDHEU) results in substantially improved paper wet strength and lower paper water absorbency. The present study examined the efficiency of chemical crosslinking treatments with CA and with mDMDHEU to decrease the biodegradation rate of laboratory paper sheets and a sack paper, both made of kraft fibers. The biodegradation was examined using a 48-h enzymatic degradation test and a 2-month soil burial test. The results indicate that chemical crosslinking is an effective non-biocidal method for making sulphate kraft paper more resistant to biodegradation. In some end-uses, improved resistance to biodegradation, along with improved paper wet performance, can enhance paper performance comparable to plastic films.